Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge studies in contemporary philosophy, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"-- Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Relational Knowing and Epistemic Injustice: Toward a Theory of Willful Hermeneutical Ignorance - Pohlhaus, Gaile (Hypatia, 2012)
I distinguish between two senses in which feminists have argued that the knower is social: 1. situated or socially positioned and 2. interdependent. I argue that these two aspects of the knower work in cooperation with each other in a way that can produce willful hermeneutical ignorance, a type of epistemic injustice absent from Miranda Fricker's Epistemic Injustice. Analyzing the limitations of Fricker's analysis of the trial of Tom Robinson in Harper Lee's To Kill a Mockingbird with attention to the way in which situatedness and interdependence work in tandem, I develop an understanding of willful hermeneutical ignorance, which occurs when dominantly situated knowers refuse to acknowledge epistemic tools developed from the experienced world of those situated marginally. Such refusals allow dominantly situated knowers to misunderstand, misinterpret, and/or ignore whole parts of the world.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; histoire et politique; ignorance herméneutique; injustices herméneutiques; injustices épistémiques; justice sociale; patriarcat; philosophie; privilèges; racisme; sciences humaines; systèmes d'oppressions; thématiques; éthique

De l'usage épistémologique et politique des catégories de « sexe » et de « race » dans les études sur le genre - Dorlin, Elsa (Cahiers du Genre, 2005)
À partir d’une réflexion sur le black feminism , cet article traite de l’articulation entre domination de genre et racisme, en tant qu’elle constitue l’un des enjeux théoriques et politiques les plus importants du féminisme anglo-saxon : dans quelle mesure l’expérience de la ségrégation raciste modèle celle du sexisme et met à mal l’unité politique du féminisme ? Si le sujet idéologique « femme » a implosé sous la critique du patriarcat, qu’en est-il du sujet politique du féminisme lui-même, « Nous les femmes » ? Notre thèse consiste à montrer comment les discours de la domination mettent à disposition des groupes opprimés des cadres anhistoriques qui réifient sans cesse ces mêmes groupes, jusque dans leurs affirmations positives. Dans ces conditions, en voulant déessentialiser le sujet du féminisme, « les femmes », le risque est de le renaturaliser en une myriade de sous-catégories (les femmes noires, les femmes voilées, les femmes migrantes...) qui deviennent des préalables aux luttes. De notre capacité à révéler l’historicité de l’entremêlement des catégories de « sexe » et de « race » et à user de techniques de tumultes à même d’inventer un autre langage politique, dépend notre capacité d’agir et de se penser comme sujets politiques en devenir.
Keywords: afro-féminisme; approches et analyses; cours; cycles supérieurs; discipline; fem9000; féminismes noirs; har4610; histoire et politique; intersectionnalité; patriarcat; racisme; ressource en ligne; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; épistémologie